2017
DOI: 10.1051/0004-6361/201630331
|View full text |Cite
|
Sign up to set email alerts
|

Subarcsecond imaging of the water emission in Arp 220

Abstract: Europe PMC Funders GroupResults-We detect 183 GHz H 2 O and 325 GHz water emission towards the two compact nuclei at the center of Arp 220, being brighter in Arp 220 West. The emission at these two frequencies is compared to previous single-dish data and does not show evidence of variability. The 183 and 325 GHz lines show similar spectra and kinematics, but the 22 GHz profile is significantly different in both nuclei due to a blend with an NH 3 absorption line.Conclusions-Our findings suggest that the most li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…The predicted size and line intensities of each nucleus, therefore, are half of our modeled values, if they are assumed to be equal. We note that recent high spatial resolution observations of H 2 O with ALMA, however, showed that 2/3 of the highexcitation water emission is emitted by the western nucleus (König et al 2017). It is worth noting that strong selfabsorption has been detected at the centers of both nuclei, where CO = -J 6 5, HCN, and CS lines show doublepeaked velocity profiles in both nuclei (Rangwala et al 2015;Scoville et al 2015;Wang et al 2016).…”
Section: B9 Arp 220mentioning
confidence: 64%
See 1 more Smart Citation
“…The predicted size and line intensities of each nucleus, therefore, are half of our modeled values, if they are assumed to be equal. We note that recent high spatial resolution observations of H 2 O with ALMA, however, showed that 2/3 of the highexcitation water emission is emitted by the western nucleus (König et al 2017). It is worth noting that strong selfabsorption has been detected at the centers of both nuclei, where CO = -J 6 5, HCN, and CS lines show doublepeaked velocity profiles in both nuclei (Rangwala et al 2015;Scoville et al 2015;Wang et al 2016).…”
Section: B9 Arp 220mentioning
confidence: 64%
“…In the case of Arp 220 the ground-state (and low-excitation) absorption feature displays a velocity dispersion that is much narrower than those of the medium-excitation emission lines (~-FWHM 226 km s 1 compared to FWHM~-412 km s 1 ), but in good agreement with the width of the high-excitation lines (~-FWHM 235 km s 1 ). High spatial resolution ALMA imaging by König et al (2017) finds that most of the highexcitation H 2 O line emission stems from the western nucleus, which is also suspected to harbor a buried AGN (Downes & Eckart 2007). The velocity centroid of the H 2 O absorption is consistent with that arising from the western source.…”
Section: The Implication Of Line Profilesmentioning
confidence: 88%
“…are surprisingly similar over ten years, given that maser emission can display high variability. König et al (2017) conclude that the emission is associated with star formation, and that the line profile is composed of the emission of many unresolved maser features that, on average, result in approximately constant flux.…”
Section: Arp 220mentioning
confidence: 86%
“…Arp 220 has a double nucleus with a projected separation of about 1.1 arcsec, for example (Scoville et al 2016), and these are clearly apparent in the Band 5 data (Humphreys et al 2017). König et al (2017) compared the ALMA H 2 O 183 GHz line with that observed using the IRAM 30 m and APEX telescopes (see Cernicharo et al 2006 and Galametz et al 2016 respectively). The line profiles Fig.…”
Section: Arp 220mentioning
confidence: 99%
“…Collisional excitation or pumping from a strong radiation field can lead to population inversion, which can create the conditions needed for bright maser emission to occur (Neufeld et al 1994). Extra-galactic H 2 O masers can be produced by a large number of individual masers in an intense starburst (Cernicharo et al 2006;König et al 2017). However, they are more typically associated with AGN, where synchrotron emission from the radio core can penetrate the large column densities of dust and gas in the circumnuclear region, and provide sufficient continuum luminosity to reach the critical threshold for E-mail: stacey@mpa-garching.mpg.de maser emission.…”
Section: Introductionmentioning
confidence: 99%